Depression and Anxiety in Chronic kidney disease Patients on Hemodialysis - Hajseyed Javadi, Alireza; Shafikhani, Ali Akbar; Allami, Abbas; Charkhchian, Malihe; Shiraghaee, Mohsen (International Journal of Applied Behavioral Sciences, 2018)
Background: Diagnosis and treatment of anxiety and depression during the early stages of chronic kidney disease is very important. This study aims to assess the true pattern of symptoms of depression and anxiety in hemodialysis population in the city of Qazvin.Methods: For this purpose, 80 individuals (40 hemodialysis patients and 40 individuals as the control group) have participated in this study. All participants completed Beck Depression Inventory and Cattell Anxiety Inventory. Additionally, clinical status, socio-economic and demographic variables of patients have been collected and analyzed by appropriate statistical methods.Results: In examining the variables of depression in terms of the maximum mild depression there has been 14 hemodialysis patients (35%) versus 34 (85%) individuals from the control group, in terms of moderate depression-severe index there has been 26 (65%) versus 6 (15%), (p<0.001). Regarding the anxiety variable in terms of the maximum mild anxiety there has been 23 (57.5%) hemodialysis patients versus 33 (82.5%) individuals from the control group, in terms of moderate-severe anxiety there has been 17 (42.5%) versus 7 (17.5%) (p=0.015). Among symptoms, depression had a significant correlation with diabetes, high blood pressure, and duration of dialysis (p<0.05). Regarding anxiety, this significant correlation has only seen with the duration of dialysis.Conclusion: The current study showed that the prevalence of depression and anxiety in hemodialysis patients are significant and correlates with clinical variables, so for improving this clinical concern, effective interventions for mental health should take place and the impact of these interventions should be investigated.